2022
DOI: 10.1021/acsnano.2c04590
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Modulated Plasmonic Scattering of Hybrid Nanorods for FFT-Weighted OCT Imaging in NIR-II

Abstract: We report a method for fast Fourier transform (FFT)-weighted optical coherence tomography (OCT) in the second biological tissue transparency window by actively modulating the plasmonic scattering of Fe3O4@Au hybrid nanorods using magnetic fields. Instead of tracking the nanoparticles’ lateral displacement in conventional magnetomotive OCT imaging, we monitor the nanorod rotation and optical signal changes under an alternating magnetic field in real time. The coherent rotation of the nanorods with the field pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Extensive overgrowth of Au on the seeds produces core–shell structures (i) that display magnetically tunable scattering properties under the irradiation of polarized light (ii). Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Deformable Polymer Confinementmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive overgrowth of Au on the seeds produces core–shell structures (i) that display magnetically tunable scattering properties under the irradiation of polarized light (ii). Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Deformable Polymer Confinementmentioning
confidence: 99%
“…28,29 Recently, we demonstrated the use of Fe 3 O 4 @Au NRs as active contrast agents for optical coherence tomographic (OCT) imaging, generating strong scattering signals by magnetically switching on their longitudinal resonance mode (Figure 6e). 28 In another effort, we have shown that the strong absorption associated with their longitudinal mode can lead to local heating, producing ultrasound signals for photoacoustic imaging when a pulsed laser is used as the light source. 29 In both cases, the imaging modalities can be enhanced or deactivated by controlling the nanorod orientation using magnetic fields, allowing effective minimization of background noises through simple pixel subtraction.…”
Section: ■ Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking nanorods for example, depending on the relative orientation of the nanorods to the polarization of the light, their LSPR has longitudinal and transverse modes [ 115 , 116 ]. These interesting optical properties have been used for developing high-performance mechanochromic and thermochromic sensors [ 116 , 117 ] or smart imaging contrast agents in photoacoustic imaging and optical coherence imaging [ 118 , 119 ]. The resonant frequency of plasmonic nanostructures is also highly susceptible to surrounding environments.…”
Section: Responsive Nanostructured Materials For Viral Disease Biosen...mentioning
confidence: 99%
“…Moreover, integrating optical materials into magnetic nanorods through surface coating or attachment techniques allows the magnetic manipulation of their optical characteristics. [11][12][13] This approach opens doors to developing stimuli-responsive chiroptical materials, incorporating responsive mechanisms that pave the way for practical applications in chiral sensing, optical display and information encryption. This paper reviews our recent progress in the field of magnetic field-induced chiral superstructures, highlighting their dynamic assembly, and the vast potential of these structures in practical applications.…”
Section: Introductionmentioning
confidence: 99%